ANALISIS BIAYA PENGENDALIAN GULMA MANUAL PADA TANAMAN BELUM MENGHASILKAN (TBM) DI PT. SENTOSA KALIMANTAN JAYA - Setia Budi; Rusli Anwar; Rusmini (JURNAL AGRIMENT, 2020)
This research is based on the background that weeds in oil palm plantations must be controlled so that economically it does not affect production. The implementation of manual weed control on immature plants (TBM) must have used costs that must be incurred by the company.This study aims to analyze the cost of controlling weeds manually and to identify the factors that affect the cost of controlling weeds in immature plants (TBM). The implementation of this research uses quantitative methods in analyzing costs at 2 work units (Afdeling) by using data on the implementation / realization of work for February-April 2019 and descriptive methods in identifying factors that affect costs by conducting field analysis. The results of the cost analysis in 2 afdeling get results in the form of the average Afdeling cost, namely: The cost of manually controlling weeds in the gawangan at Afdeling 1 is Rp. 254,756 / ha and the gawangan at Afdeling 2 is Rp. 261,242 / ha. Meanwhile, the cost of controlling weeds manually on the plate at Afdeling 1 is Rp. 254,483 / ha and the plate at Afdeling 2 Rp. 238,787 / ha. Factors that influence the cost of controlling weeds manually in immature plants (TBM), especially in the dish and in the fields are more due to factors of land topography, weed density, and the types of weeds that are controlled.